Vitamin E intake and multiple health outcomes: an umbrella review - Zhang, Tianyi; Yi, Xianyanling; Li, Jin; Zheng, Xiaonan; Xu, Hang; Liao, Dazhou; Ai, Jianzhong (Frontiers in Public Health, 2023)
Background: The benefits of vitamin E (VE) for multiple health outcomes have been well evaluated in many recent studies. Objective: The purpose of this umbrella review was to conduct a systematic evaluation of the possible associations between VE intake and various health outcomes. Methods: We systematically searched PubMed, Embase, and Web of Science to identify related meta-analyses of observational studies and randomized trials. We estimated the effect size of each association by using random or fixed effects models and the 95% confidence interval. We use standard approaches to evaluate the quality of the articles (AMSTAR) and classify the evidence into different levels of quality (GRADE). Results: A total of 1974 review articles were searched, and 27 articles with 28 health outcomes were yielded according to our exclusion criteria. VE intake was inversely associated with the risk of breast cancer, lung cancer, esophageal cancer, gastric cancer, pancreatic cancer, kidney cancer, bladder cancer, cervical neoplasm, cardiovascular disease, Parkinson’s disease, depression, age-related cataract, metabolic syndrome, and fracture. Overall, most of the quality of the evidence was low or very low. Three of them (stroke, Age-related cataract, obesity) were identified as “moderate” quality. The AMSTAR scores of all health outcomes ranged from 5 to 10. Conclusion: Our study revealed that VE intake is beneficially related to multiple health outcomes. However, future studies on recommended doses and recommended populations of VE are also needed.